The Basic Movements of Running 60-Metres in Elementary School Students: Achievement of Play Approaches - Yasriuddin; Juhanis; B, Risman; Wahyudin; Hudain, Muh. Adnan (Education and Talent Development Center Indonesia (ETDC Indonesia), 2024)
This study aims to determine whether a play approach improves learning outcomes for basic 60-meter running movements in class V Elementary School Lariang Bangi 1 Makassar. This study employed a classroom action research (PTK) approach, utilizing two cycles. In this research, the independent variable is the playing approach, while the dependent variable is the result of learning the basic movements of the 60-meter run. The population of this research was all 30 students of class V of Lariang Bangi 1 Makassar Elementary School; the sample was drawn using a total sampling technique. We collected the research data by implementing a play-based approach and monitoring the student's progress in mastering the fundamental movements of running 60 meters. We used descriptive statistics, along with percentages, as the data analysis technique. The study findings revealed that using the play method in the basic movement test of running 60 meters could improve the learning outcomes of class V students at Lariang Bangi 1 Makassar State Elementary School. Cycle I to cycle II scores demonstrate the improvement in learning outcomes for the basic movements of running 60 meters. In cycle I the completion value was 67%, and in cycle II it was 87%. The average value of learning outcomes for the basic movements of running 60 meters also increased, reaching 74 in cycle I and 82 in cycle II. Based on these findings, we can deduce that class V students Elementary School experienced a rise in learning outcomes for the fundamental movements of running 60 meters using a play-based approach.